2014
DOI: 10.1016/j.kjms.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of shock wave therapy in patients with knee osteoarthritis and popliteal cyamella

Abstract: This randomized, controlled study was performed to compare the effects of extracorporeal shockwave therapy (ESWT) and ultrasound on the rehabilitation of knee osteoarthritis with popliteal cyamella. One hundred and twenty patients with bilateral moderate knee osteoarthritis (Altman III) and popliteal cyamella were selected and randomly assigned to four groups (GI-GIV). Patients in Groups I-III received isokinetic muscular strengthening exercises three times weekly for 8 weeks. Group II received pulse ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 34 publications
3
103
0
4
Order By: Relevance
“…Wang et al13 ) reported extracorporeal shock waves were effective in preventing and treating knee arthritis in rats with knee arthritis. Chen et al14 ) conducted a comparative study in which ESWT and ultrasound therapy were applied to patients with knee arthritis for eight weeks, and they reported that the group in which ESWT was applied showed reduction in pain, Lequesne index scores and increasing in the range of motion. The present study also showed statistically significant declines in the VAS and K-WOMAC scores of the ESWTG.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al13 ) reported extracorporeal shock waves were effective in preventing and treating knee arthritis in rats with knee arthritis. Chen et al14 ) conducted a comparative study in which ESWT and ultrasound therapy were applied to patients with knee arthritis for eight weeks, and they reported that the group in which ESWT was applied showed reduction in pain, Lequesne index scores and increasing in the range of motion. The present study also showed statistically significant declines in the VAS and K-WOMAC scores of the ESWTG.…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al . ,b). In patients with shoulder adhesive capsulitis, those treated with ESWT had improved range of motion and ability to perform daily activities faster than those patients treated with oral steroids (Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SW improves joint function, reduces inflammatory cytokines which are responsible for osteoarthritic degeneration and enhances the recovery effects 13 . Recently, three clinical studies support the potential therapeutic utility of SW in the treatment of OA [21][22][23] .IL-10 inhibits the synthesis of different pro-inflammatory cytokines (IFN-γ, IL-2, IL-3, TNF-α and GM-CSF) which are hyper-expressed in arthritic conditions. The overexpression of N-Cadherin and β-Catenin is associated with degeneration diseases 24 .…”
Section: Discussionmentioning
confidence: 99%